A simplified chemical reduction method for preparation of graphene: Dispersity, reducibility and mechanism. Issue 16 (December 2016) - Wang, Rong; Liu, Yan; Zhang, Yanzong; Wang, Lilin; Yang, Gang; Shen, Fei; Deng, Shihuai; Zhang, Xiaohong; He, Yan; Luo, Ling
Abstract: Graphene was prepared by a simple chemical reduction of graphite oxide in the dimethylacetamide (DMAc)/H2 O mixture solvent. The results from Fourier transform infrared spectroscopy, Raman spectroscopy and X-ray photoelectron spectroscopy indicated that the reduction degree of graphene products increased with the increase in the volume ratio of DMAc and water (VDMAc /VH2O ), and kept constant when the VDMAc /VH2O ratio was equal or greater than 1. A reduction mechanism from graphite oxide to graphene was proposed. The epoxy groups and hydroxyl on the graphite oxide (GO) surface could be eliminated in the reduction process, whereas the carbonyl was converted to a hydroquinone structure.